The Role of Parents in the Physical-Motor Development of Elementary School Age Children During the Covid-19 Pandemic - Rakhimafa Wulandari, Dea; Rahma Fadhila, Aisya (Jurnal Paradigma, 2021)
The world was shocked by the emergence of a disease outbreak that attacks the human respiratory system by WHO corona virus. Corona virus has an extraordinary impact in all fields, including education. Many schools and universities are closed to break the chain of distribution, so the government implements learning programs from home. This study aims to analyze the role of parents in the corona pandemic towards the motor physical development of elementary school- age children. This research uses qualitative research library research methods. The results of his research are parents play an important role in the physical development of motoric children of primary school age during the co-19 pandemic. The role is as a caregiver and educator, mentor, motivator, and facilitator.